Reinforced revenue sharing contract thru sharing in sale point by adopting semi-TDPD. Issue 4 (1st April 2020) - Shafiei, Mahdi; Modarres, Mohammad
In this paper, we develop a new coordination contract of manufacturer-retailer in a distribution system. A revenue sharing contract that sharing the revenue between the distribution systems members at sale point as coefficient of product price which integrated semi third degree price discrimination (semi-TDPD) into the model. Semi-TDPD strategy makes it possible to exploit the opportunity of customers' behaviour that they willing to pay different price to owning the product and bargaining for lower price, by adopting price discrimination strategy. To illustrate the proposed approach, we present some numerical examples. Through these examples, we investigate the impact semi-TDPD on decision variables as well as the well performance of proposed revenue sharing coordination.